A rapid IL-17 response to Cryptosporidium parvum in the bovine intestine - Drinkall, Emma; Wass, Matthew J.; Coffey, Tracey J.; Flynn, Robin J. (Elsevier, 2017)
Cryptosporidium parvum causes diarrhoea, due to villi damage, in livestock and humans globally. Immunity develops after repeated infections but initial infections can be severe, highlighting the importance of early infection dynamics. We have modelled early C. parvum infection in bovine jejunum biopsies. IL-17A accumulated over time peaking at 9 h post-infection, with no effect of infection on IL-1β; antibiotics positively influenced IL-17A as higher levels were found in cultures with antibiotics. Infection of primary fibroblasts resulted in lower plaque formation when fibroblasts were primed with IL-17A. Our results indicate a role for IL-17A in reducing C. parvum-dependent host cell damage.